Update on Targeted Therapy in Medullary Thyroid Cancer - Okafor, Christian; Hogan, Julie; Raygada, Margarita; Thomas, Barbara J.; Akshintala, Srivandana; Glod, John W.; Del Rivero, Jaydira (Frontiers in Endocrinology, 2021)
Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor that accounts for 2-4% of all thyroid cancers. All inherited MTC and approximately 50% of sporadic cases are driven by mutations in the REarranged during Transfection (RET) proto-oncogene. The recent expansion of the armamentarium of RET-targeting tyrosine kinase inhibitors (TKIs) has provided effective options for systemic therapy for patients with metastatic and progressive disease. However, patients that develop resistant disease as well as those with other molecular drivers such as RAS have limited options. An improved understanding of mechanisms of resistance to TKIs as well as identification of novel therapeutic targets is needed to improve outcomes for patients with MTC.